Peningkatan Digital Pedagogy Guru Sekolah Dasar Melalui Multimedia Interaktif Lectora dan Genially - Aldina Eka Andriani; Sri Sulistyorini; Yuli Witanto; Siti Maryatul Kiptiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Teachers must have the ability to align learning objectives with students’ diverse characteristics in the digital era; therefore, teachers’ classroom management skills need to be improved, especially in mastering, analyzing, and wisely utilizing technology-based learning media. This community service activity aims to provide knowledge insights and improve digital pedagogy by creating interactive multimedia through training and mentoring using the Genially application in learning for elementary school teachers at the Pringgodani Cluster Teachers’ Working Group (KKG) in Semarang. The methods used include lectures, pre-tests and post-tests, training and mentoring, demonstrations, simulations, and assignments. The results of the community service implementation show an improvement in teachers’ knowledge and skills in creating interactive multimedia, as evidenced by the average pre-test score of 56.08% and post-test score of 84.13%, indicating an increase of 28.1%. This community service activity concludes that the training and mentoring on the development of interactive multimedia using Genially in IPAS learning improves the knowledge and digital pedagogy of elementary school teachers at the Pringgodani Cluster Teachers’ Working Group (KKG) in Semarang.